An assessment of the impacts of electronic ticketing on inspections and material procurement for highway construction - Subramanya, Karthik; Kermanshachi, Sharareh; Pamidimukkala, Apurva; Loganathan, Karthikeyan (Frontiers in Built Environment, 2023)
Both the construction inspection process and the material supply have shown to benefit from the use of technological advancements and digitalization. Despite the availability of numerous technologies to assist construction inspection and material delivery, there is a lack of understanding regarding the appropriate application of mobile technology for highway construction. This study aims to (1) assess the merits of the e-Ticketing technology based on the benefits it provides, and (2) determine the amount of time that inspectors save as a direct result of e-Ticketing adoption. A structured survey questionnaire was designed and distributed to ascertain the views of those working in the highway construction industry on the advantages and potential time savings. The research rated the advantages of e-Ticketing deployment and estimated the approximate time savings based on the 53 responses obtained from a variety of state DOTs. When the required number of inspectors was compared before and after the implementation of e-Ticketing, it was discovered that projects that required multiple inspectors could reduce their workforce by 24% by implementing e-Ticketing. This study contributes to the existing body of knowledge by investigating the opportunities for state departments of transportation to improve workforce productivity, increase workforce safety and morale, minimize schedule delays, be prepared for the next pandemic, if there is one, and minimize the shortage of inspection staff.